Remote Psychotherapy During the COVID-19 Pandemic. Experiences With the Transition and the Therapeutic Relationship. A Longitudinal Mixed-Methods Study - Stefan, Robert; Mantl, Gerd; Höfner, Claudia; Stammer, Julia; Hochgerner, Markus; Petersdorfer, Kathrin (Frontiers in Psychology, 2021)
Aims: Research conducted prior to the onset of the COVID-19 pandemic indicates that remote psychotherapy is as effective as in-person treatment. At that time, it usually was the therapist’s individual choice to work remotely, whereas the pandemic pushed psychotherapists, including previous skeptics, to incorporate remote work methods into their routine due to limited face-to-face contact. There is little knowledge of the way therapists experienced this sudden and forced transition to remote psychotherapy as the only treatment option. The present study aims to assess psychotherapists’ experience and proficiency delivering remote psychotherapy as well as to investigate perceived changes in the psychotherapeutic relationship. Method: An online survey was administered to psychotherapists of the Austrian Association for Group Therapy and Group Dynamics (ÖAGG). Three test periods (t) were set (t1: April, 2020 with N = 175; t2: May–June, 2020 with N = 177; t3: November–December, 2020 with N = 113). Research was conducted longitudinally using a mixed-methods research design. Results: While psychotherapists’ levels of experience with telephone-based psychotherapy remained similar across all test periods, they became slightly more experienced using video therapy over the test period observed. However, they continued to feel less experienced compared to the use of telephone-based psychotherapy. The therapeutic relationship appeared to improve over the course of the first two test periods, while the third period showed a slight decline. No general deterioration of the psychotherapeutic relationship was found in the timespan studied. Conclusion: Despite many challenges and concerns, psychotherapists seem to adapt and enhance their skills in remote psychotherapy over time. The present paper confirms and enhances previous findings in the field due to its longitudinal approach. Remote psychotherapy can be a credible and trustworthy alternative to in-person treatment to be adopted and implemented on principle by a majority of psychotherapists regardless of their orientation. Furthermore, it sheds light on chances, problems und general observations regarding the comprehensive provision of remote psychotherapy in a pandemic situation.